PENINGKATAN PENGHASILAN PEREMPUAN SUKU MUYU DENGAN PEMBUATAN PINDANG IKAN PARI - Ermelinda Agnes Gunu Pure; Indah Widanarti (Musamus Devotion Journal, 2019)
Muyu tribe comes from Boven Digoel Regency which inhabits a large part of the region and of Merauke Regency. The female sellers of the Muyu tribe of Domba village of Merauke regency are a small proportion of Muyu women who are in trading bussines in Merauke market to support the family economy. The importance of improving their welfare and how to manage the household economy are highly dreamed so that it was sufficient. Therefore, through the problem identification approach, the location survey, a literature study, it was found a solution to increase the income of Muyu tribe women that it was found that stingrays were abundant in Merauke and the price was relatively cheap and has not been processed into ready-to-eat food for sale, besides that the human resource of the female sellers of Muyu tribe in improving welfare was still lacking. Then the training and assistance results show that: 1) abundant stingrays in Merauke can be used well if processed into nutritious delicacies. 2) One of the efforts to help human resources, that is the Muyu tribes in improving their personal and family welfare, can be done by involving them in training and mentoring programs. 3) By processing the stingrays can increase the selling value of stingrays by processing stingrays to become Pindang stingray. Key words: increased income, Pindang stingray, Muyu women